The association of family history with the risk of lung cancer: a pooled analysis of case-control studies: 10.55131/jphd/2025/230323 - Widiyanto, Aris; Joel Rey Acob; Rita Benya Adriani; Adhani Windari; Ayu Anulus; Sukandriani Utami; Asruria Sani Fajriah; Joko Tri Atmojo (Journal of Public Health and Development, 2025)
The risk of lung carcinoma is influenced by genetic predisposition and other risk factors. This study aimed to explore the association between a family history of any type of cancer and the risk of lung carcinoma through a pooled analysis of case-control studies. A systematic literature search was performed across Google Scholar, PubMed, and Science Direct up to January 31, 2024. Eight observational case-control studies met the inclusion criteria, which required multivariate logistic regression analysis and a focus on familial cancer history. Using Review Manager software, pooled estimates and 95% confidence intervals were calculated. Out of 603 identified studies, eight were included. The meta-analysis found that individuals with a family history of cancer had a significantly higher risk of lung cancer (aOR = 1.64; 95% CI = 1.17–2.29; p = 0.004). These findings highlight the need for targeted screening and early detection strategies for high-risk individuals.